Mediasi Menurut Hukum Perdata dan Hukum Islam dalam Sengketa Pengasuhan Anak - Gema Rahmadani; Sukiati Sukiati; Nurasiah Nurasiah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The role of a mediator is crucial in facilitating understanding among parties involved in a dispute. Mediators aid the parties in comprehending each other's perspectives regarding the contested issues and subsequently assist them in making objective assessments of the overall situation during negotiation processes. This research specifically aims to identify the legal standing, both in civil law and Islamic law, concerning the disputed issue of child custody with the assistance of a neutral third party (mediator). The research employs a qualitative method, involving the collection, analysis, and comprehensive interpretation of narratives. Legal materials obtained from literature reviews and legal approaches are analyzed using systematic interpretation techniques. The research findings highlight that the mediator's ability significantly influences the success of mediation. If mediation fails to reach an agreement, the mediator submits a written notification to the presiding judge, who then informs the panel judge handling the case. The disputing parties are expected to appear at the scheduled hearing, and the trial process continues as usual.